What Oregon's Parity Law Can Tell Us about the Federal Mental Health Parity and Addiction Equity Act and Spending on Substance Abuse Treatment Servicesb - McConnell, K. John (2012)
BACKGROUND: The Paul Wellstone and Pete Domenici Mental Health Parity and Addiction Equity Act of 2008 (MHPAEA) requires commercial group health plans offering coverage for mental health and substance abuse services to offer those services at a level that is no more restrictive than for medical-surgical services. The MHPAEA is notable in restricting the extent to which health plans can use managed care tools on the behavioral health benefit. The only precedent for this approach is Oregon's 2007 state parity law. This study aims to provide evidence on the effect of comprehensive parity on utilization and expenditures for substance abuse treatment services. METHODS: A difference-in-difference analysis compared individuals in five Oregon commercial plans (n=103,820) from 2005–2008 to comparison groups exempt from parity in Oregon (n=19,633) and Washington (n=39,447). The primary outcome measures were annual use and total expenditures. RESULTS: Spending for alcohol treatment services demonstrated statistically significant increase in comparison to the Oregon and Washington comparison groups. Spending on other drug abuse treatment services was not associated with statistically significant spending increases, and the effect of parity on overall spending (alcohol plus other drug abuse treatment services) was positive but not statistically significant from zero. CONCLUSIONS: Oregon's experience suggests that behavioral health insurance parity that places restrictions on how plans manage the benefit may lead to increases in expenditures for alcohol treatment services but is unlikely to lead to increases in spending for other drug abuse treatment services.